1998
DOI: 10.1111/j.1469-7793.1998.679bv.x
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen‐dependent K+ fluxes in sheep red cells

Abstract: This study was designed to investigate the O2 dependence of K+ influx in sheep red cells. Influx was determined using 86Rb+ as a tracer for K+; glass tonometers coupled to a gas mixing pump were used to equilibrate cell samples to the requisite oxygen tension (PO2). Both volume‐ and H+‐stimulated K+ influxes in low potassium‐containing (LK) sheep red cells were approximately doubled on equilibration with O2 relative to influxes measured in N2. O2‐dependent influxes were abolished when Cl− was replaced with NO3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 32 publications
3
25
0
Order By: Relevance
“…The K¤ influx stimulated by Mg¥ depletion was abolished by Cl¦ substitution and also by treatment with calyculin A. Oµ-dependent K¤-Cl¦ cotransport was also observed by Motais and coworkers after Mg¥ clamping trout red cells (Borgese et al 1991), and we have previously shown that the same occurs in LK sheep red cells (Campbell & Gibson, 1998a), a system commonly used to study K¤-Cl¦ cotransport. Subsequently, however, we found that changes in free [Mg¥]é of a magnitude similar to that occurring physiologically during oxygenation-deoxygenation cycles (a few hundred micromolar), had very little effect on the cotransporter.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The K¤ influx stimulated by Mg¥ depletion was abolished by Cl¦ substitution and also by treatment with calyculin A. Oµ-dependent K¤-Cl¦ cotransport was also observed by Motais and coworkers after Mg¥ clamping trout red cells (Borgese et al 1991), and we have previously shown that the same occurs in LK sheep red cells (Campbell & Gibson, 1998a), a system commonly used to study K¤-Cl¦ cotransport. Subsequently, however, we found that changes in free [Mg¥]é of a magnitude similar to that occurring physiologically during oxygenation-deoxygenation cycles (a few hundred micromolar), had very little effect on the cotransporter.…”
Section: Discussionsupporting
confidence: 74%
“…In most experiments, samples were deoxygenated for 60 min and then either held in Nµ or incubated with Oµ for 15 min before dilution into saline at low haematocrit (about 5%) pre-equilibrated and maintained at the requisite POµ for influx measurement, alteration of [Mg¥]é or pH determinations, as appropriate (see Campbell & Gibson, 1998a, for details). In most experiments, samples were deoxygenated for 60 min and then either held in Nµ or incubated with Oµ for 15 min before dilution into saline at low haematocrit (about 5%) pre-equilibrated and maintained at the requisite POµ for influx measurement, alteration of [Mg¥]é or pH determinations, as appropriate (see Campbell & Gibson, 1998a, for details).…”
Section: Tonometrymentioning
confidence: 99%
“…Unlike the complete inactivation and volume-and pH-insensitivity of K-Cl cotransport in trout [81] and equine [68] RBCs under deoxygenation, K-Cl cotransport in deoxygenated sheep erythrocytes is active and volume-and pH-sensitive [49]. Nevertheless, oxygenation of sheep RBCs affects K-Cl cotransport by increasing both its rate and the degree of its volume-and pH-dependence [49]. It is noteworthy that K-Cl cotransport in sheep erythrocytes seems to be controlled by two signals of cell swelling, a reduction in macromolecular crowding and a putative mechanical signal [112].…”
Section: Hb Oxygenation and Volume Regulationmentioning
confidence: 99%
“…Similar evidence is provided by sheep Hb that exhibits low DPG binding and hence may not be expected to bind to negatively charged tails of proteins. Nevertheless, KCl cotransport in sheep RBCs has been shown to be O 2 -sensitive [49].…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation